2017
DOI: 10.1148/radiol.2016152509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time-of-Flight Information on PET/MR Reconstruction Artifacts: Comparison of Free-breathing versus Breath-hold MR-based Attenuation Correction

Abstract: Purpose To evaluate the magnitude and anatomic extent of the artifacts introduced on positron emission tomographic (PET)/magnetic resonance (MR) images by respiratory state mismatch in the attenuation map. Materials and Methods The method was tested on 14 patients referred for an oncologic examination who underwent PET/MR imaging. The acquisition included standard PET and MR series for each patient, and an additional attenuation correction series was acquired by using breath hold. PET data were reconstructed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The contribution of TOF was evaluated. PET quantification errors with non-TOF reconstructions were significantly higher than the errors with TOF reconstructions as revealed by a paired t-test (details in the results section), in agreement with other recent studies (Conti 2010, Mehranian A and Zaidi H 2015, Delso et al 2017.…”
Section: Discussionsupporting
confidence: 91%
“…The contribution of TOF was evaluated. PET quantification errors with non-TOF reconstructions were significantly higher than the errors with TOF reconstructions as revealed by a paired t-test (details in the results section), in agreement with other recent studies (Conti 2010, Mehranian A and Zaidi H 2015, Delso et al 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that TOF information improves image quality of PET/CT [ 24 – 28 ] and PET/MRI [ 29 – 31 ]. For example, the implementation of TOF in PET/MRI notably reduces image acquisition time [ 32 ], metal artifacts [ 31 , 33 35 ], as well as artifacts caused by respiratory mismatch between emission and data [ 21 , 36 ]. Using the same TOF PET images from PET/CT with MRI or CT in a trimodality setting showed that the PET/CT and PET/MRI performed comparable in whole-body oncology [ 37 ], but for PET/MRI, the addition of TOF improved lesion quantification [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is now being actively pursued with the emergence of time-of-flight (ToF) PET/MRI systems. Yet, even without MLAA, improved image quality can be achieved by the use of improved ToF in regular ToF OSEM and it was shown that ToF already mitigates MR-based attenuation correction artefacts [ 21 ].
Fig.
…”
Section: Dialogue Boardsmentioning
confidence: 99%